Analisis Resource Leveling Menggunakan Precedence Diagram Method (PDM) pada Gedung Mako Lanal Balikpapan - Pandya, Manikmaya Wibana Yajuh; Nasution, Diffa Salsa Devana; Hendriyanti, Irna; Pratiwi, Reno (Jurnal Talenta Sipil, 2024)
The construction of the Mako Lanal building is to realize the fulfillment of the needs of facilities and facilities / infrastructure to support the main tasks and functions of the Navy. With the planned cost of this building construction project amounting to IDR 11,884,285,000.00. With a duration of 210 days starting on May 06 - December 01, 2021. Researchers conducted rescheduling using the Precedence Diagram Method (PDM) using the Microsoft Project 2016 program. The results of the calculation of the amount of labor before the leveling of labor are uneven and fluctuations occur, with a maximum workforce of 76 workers. therefore, the leveling of labor will be carried out. By rescheduling the relationship between jobs. after smoothing the workforce the maximum number after smoothing is 38 workers.